School hearing health actions in the municipality of Sobral-CE: perception of speech therapists - doi: 10.5020/18061230.2012.p228 - Rafaela Bezerra Façanha Correia; Joyce Monte Silva Coelho (Universidade de Fortaleza, 2012)
Objective: To evaluate the school hearing health actions developed in the Listen Sobral Project. Methods: Qualitative study, conducted at the Department of Hearing Health Care (SASA) of the city of Sobral - CE, Brazil, from April to June, 2010. Study participants were the Listen Sobral Project's coordinator and four speech therapists attending Multidisciplinary Residency in Family Health, working in partnership with the project. Data collection was performed through semi-structured interviews, adopting the technique of content analysis according to the convergence of speech, in which the categories emerged: school hearing health actions; benefits from the actions; difficulties in developing the actions; and changes for improvement in the actions. Results: According to discourse of speech therapists, one realizes that school hearing health actions are developed centered on health promotion, prevention and early identification of hearing loss. However, weak points were identified, especially regarding the teacher training; partnership between school and speech therapists; ear, nose and throat care; and suitable facilities. Conclusion: School hearing health actions have become part of reality in the city of Sobral, although not yet fully at the present time. It is therefore necessary to maintain these actions, but with some changes toward the elaboration of a more organized structure, in order to promote care of superior quality for school children.